Expression analysis of CsNAC30 gene in cucumber under drought stress - Lei Gong; Linna Qian; Chengcheng Shen; Yuping Wei; Wenjiao Wang (Biotechnology & Biotechnological Equipment)
This study performed a bioinformatics analysis of the CsNAC30 gene and examined its expression levels in cucumber leaves and roots under drought stress induced by PEG-6000. The bioinformatics analysis showed that the open reading frame (ORF) of CsNAC30 is 1254 bp, encoding a protein consisting of 417 amino acids. This protein is relatively unstable and hydrophilic, lacks transmembrane regions, and contains 49 phosphorylation sites. It also features a conserved NAM domain at the N-terminus. Homology and phylogenetic analyses indicate that CsNAC30 is a member of the NAC transcription factor family and is most closely related to the melon CMeNAC105 and the winter melon BhNAC96. Quantitative real-time PCR (qPCR) revealed that CsNAC30 expression is induced by drought stress, with relative levels increasing in both leaves and roots following PEG treatment. Expression peaked at 6 h in leaves and 9 h in roots before decreasing. These findings suggest that CsNAC30 plays a role in the cucumber’s response to drought stress.